PENDAMPINGAN PERENCANAAN RENOVASI DESAIN SEKOLAH PAUD NURUL HIKMAH KABUPATEN PAMEKASAN - Hadi Surya Wibawanto (Jurnal Pengabdian Masyarakat Borneo, 2022)
This Abdimas activity in the form of Science and Technology for the Community (IbM) is in the form of architectural design consulting assistance in the renovation of the PAUD Nurul Hikmah School Pamekasan, East Java Province. This building is planned to be one of the centers for community education activities in Pamekasan Regency at the Early Childhood Education level. The renovation of this school is proposed for the exterior side (fence, garden, landscape, playground). This service activity has a specific purpose as an effort to provide technical assistance for architectural and civil renovations by applying building planning principles in accordance with the applicable SNI. Another goal is to support development efforts that are oriented towards educational activities. The plan of activities carried out is in the form of studying the description of the location of the abdimas, modeling architectural and civil analysis, interpreting the results and providing recommendations for the results.